Hospitality employees’ mental health issues: a review - Ghazali, Hazrina; Mohamad, Siti Fatimah; Othman, Mohd Amar Ridham; Ishak, Maisarah (HRMARS, 2024)
Mental health issues have become a serious concern in many organizations, where this problem might lead to negative outcomes for both employees and employers. Because of the COVID-19 pandemic, untreated mental health problems got worse, which had the worst effect on a person's life and work that could happen. One of the key environments that affect employees' mental health is the workplace. People are becoming more aware of and cognizant of the role that work can play in promoting or impeding mental wellness. The majority of mental health professionals concur that the workplace environment can have a considerable impact on a person's mental and physical well-being, despite the fact that it is difficult to measure the effect of work alone on a person's sense of self, self-esteem, and social recognition. (World Health Organization, Department of Mental Health) The National Health and Morbidity Survey, which was conducted every four years, was the most exhaustive survey ever conducted on a national scale. The main objective of this research is to explore the awareness and factors that influence mental health issues among hospitality employees. Findings from this review may help future researchers develop a mental health framework that can be used as a reference by managers and policymakers at the workplace among hospitality employees.